Alterations in innate immune defense distinguish first-episode schizophrenia patients from healthy controls - Chen, Song; Gou, Mengzhuang; Chen, Wenjin; Xiu, Meihong; Fan, Hongzhen; Tan, Yunlong; Tian, Li (Frontiers in Psychiatry, 2022)
Innate immune components involved in host defense have been implicated in schizophrenia. However, studies exploring their clinical utility in schizophrenia diagnosis are limited. The main purpose of this study was to evaluate whether circulating endotoxin, high mobility group box 1 protein (HMGB1) and complement component 4 (C4) could act as peripheral biomarkers to distinguish first-episode schizophrenia (FES, n = 42) patients from healthy controls (HCs, n = 35) in associations with psychopathological symptoms and cognitive dysfunctions. Also, their changes after 8-week antipsychotic treatment were investigated. The Positive and Negative Syndrome Scale (PANSS), Psychotic Symptom Rating Scale, and MATRICS Consensus Cognitive Battery were administered. Receiver operating characteristic (ROC) curves were conducted to evaluate the diagnostic effectiveness of the three biological indicators. Compared to HCs, levels of endotoxin, HMGB1 and C4 were remarkably increased in FES patients after controlling for age, gender, body mass index and education years, and the combination of the three biomarkers demonstrated desirable diagnostic performance (AUC = 0.933). Moreover, the endotoxin level was positively correlated with the severity of auditory hallucinations. After 8 weeks of treatment, HMGB1 was decreased significantly in patients but still higher than that in HCs, whereas endotoxin and C4 did not change statistically. The baseline levels of endotoxin, HMGB1 and C4, as well as their changes were not associated with changes in any PANSS subscale score and total score. Our preliminary results suggest that a composite peripheral biomarker of endotoxin, HMGB1 and C4 may have accessory diagnostic value to distinguish schizophrenia patients from HCs. Additionally, endotoxin might be implicated in the pathogenesis of auditory hallucinations.